Can regenerated inner-city areas remain sites of public-place sociability? Psycho-social processes predicting public sociability in a changing neighbourhood - Bettencourt, L.; Castro, P.; Dixon, J. (Journal of Community and Applied Social Psychology, 2021)
The processes of urban regeneration of long-disinvested inner-city neighbourhoods today happening in many European cities sometimes dramatically transform residents' traditional uses of their public places. Focusing on a neighbourhood renowned for its traditional public place sociability – Mouraria, in Lisbon – this study explored the psychosocial processes that may shape the maintenance of that sociability in the face of increasing social diversification and small-scale gentrification brought about by a mixed/bottom-up regeneration plan. A questionnaire survey (n = 201) with two types of residents (“traditional residents” and “new gentrifiers”) indicated that: (a) both types report using Mouraria's public places for socializing, although traditional residents do so to a greater degree; (b) perceived cultural continuity of the neighbourhood is positively related to public place sociability for both groups; and (c) this relationship is mediated by both place identification and place knowledge; but (d) it is not moderated by type of resident. By implication, we argue that regenerated inner-city neighbourhoods may remain as places of lively public sociability and companionship if residents are able to forge and/or retain a sense of identification with, and intimate knowledge of, the neighbourhood, and view it as maintaining continuity with the past.